Formulation of Sunscreen Body Lotion with A Combination of Chitosan and White Turmeric (Curcuma zedoaria Rosc.) - Aminati, Salmah; Putri Arini, Regita; Dyah Nuraini, Herdita; Indah Fajarwati, Febi (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2025)
In this study, body lotion was made in four formula variations from white turmeric and chitosan as natural active ingredients. The objectives of this study were determine whether chitosan could be used as a good emulsifier in body lotion, to determine whether white turmeric could be used as a sunscreen in body lotion, and to determine the physical and chemical properties of body lotion resulting from the combination of chitosan and white turmeric. Characterized results of Chitosan using FTIR and obtained functional groups, namely O-H, C-H, C=O, N-H, and C-H with a %DD value 86,47%. White turmeric simplisia was characterized using FTIR and obtained functional groups O-H, C-H, and C=O, indicating the possible presence of chromophore groups in curcumin. A phytochemical screening test result showed that white turmeric contains alkaloids and flavonoids. There were four formulation variations, namely F0, F1, F2, and F3. Physical quality tests were conducted, including organoleptic, homogeneity, pH, stability, hedonic, irritation, and SPF tests. There were two body lotion formulas that met the requirement. In the hedonic test, F0 and F1 were preferred by the respondents. The maximum SPF value of the body lotion preparation in formula F3 was 20,00487, which falls into the ultra protection category.